Representation of Inheritance Law in the Film Gara Gara Warisan - Ahmad Fauzan (Cipta Pustaka Nusantara, 2026)
Family films function as a medium of communication, entertainment, and a social mirror that reflects the dynamics and values of family life. One example is Gara Gara Warisan, an Indonesian comedy-drama that raises the issue of inheritance disputes and highlights the importance of communication, justice, and togetherness within the family. This study aims to analyze the representation of inheritance law in the film through Roland Barthes’ semiotic perspective and the Indonesian inheritance system. The research is a descriptive-qualitative study employing a semantic approach and inductive analysis, using secondary data derived from the film Gara Gara Warisan. Dialogues in the film are classified based on semiotic parameters, then analyzed using Roland Barthes’ theory and the Indonesian inheritance system to identify consistent patterns of meaning. The findings indicate that the concept of inheritance in Gara Gara Warisan presents multiple layers of meaning from Roland Barthes’ semiotic perspective and reflects the dynamics of inheritance law in Indonesia. This study implies that the understanding of inheritance law is closely related to concepts perceived by society. Such concepts must embody principles of togetherness, justice, and utility.